El nudo/nodo en la narrativa de Julio Cortázar y Los caminos hacia la hiperficción - Llosa Sanz, Álvaro (Acta Hispanica, 2010)
The word nudo (knot), which comes from the latin nodus, is explained in seventeen different ways in the Dictionary published by the Spanish Royal Academy. However, every definition converges in a key point: the knot as a juncture or convergence of diverse elements. In this paper, I apply these definitions to the analysis of knot and nodal methaporic structures used in Julio Cortázar’s narrative: the knot starts as a literary metaphor in his early work titled Divertimento (1949), it evolves into a nodal structure in Rayuela (1963), and finally it reachs a maximum complexity of knots and nodes in 62, modelo para armar (1968).